Public cooperation statements - Ann-Kathrin Koessler; Lionel Page; Uwe Dulleck (Journal of Economic Interaction and Coordination, 2021)
Communication is a well-known tool to promote cooperation and pro-social behavior. In this study, we examine whether minimal communication in form of public consent with a pre-defined cooperation statement is sufficient to strengthen cooperation in groups. Within the controlled environment of a laboratory experiment, we identify ways by which non-enforceable cooperation statements are associated with higher levels of cooperation in a public good setting. At first, the statement triggers selection; socially oriented individuals are more likely to make the cooperation statement. In addition, we can show that a behavioral change takes place once the statement is made. This change can be attributed to commitment arising from the pledge and to increased coordination between the interaction partners. Depending on the institutional context, these drivers can vary in strength. Comparing compulsory and voluntary cooperation statements, we find that both are effective in motivating higher contributions to the public good.
Keywords: A13; C72; C91; H41; 330; Cooperation; Communication; Pledge; Social dilemma; Pro-social behavior; Policy making